The racial lens of Dylann Roof: racial anxiety and white nationalist rhetoric on new media. Issue 1 (2nd January 2020) - Chebrolu, E.
ABSTRACT: This essay claims that white nationalism is a political identity animated by the affect of racial anxiety . Drawing from Frantz Fanon's work on blackness as a phobic object, Hortense J. Spillers's conception of the flesh/body distinction, and Jacques Lacan's seminar on anxiety, the essay argues that the racial anxiety of the white nationalist subject emerges from encounters with the incapacity of post-racial fantasies of national wholeness to fully disavow the abjection of blackness that holds together the symbolic structure of race. The essay performs a rhetorical analysis of Dylann Storm Roof's manifesto "rtf88, " claiming that Roof's racial anxiety is anchored by an identification with the trope of "racial awareness" as an abject metaphor for his sovereignty. The essay uses this trope to trace three different relationships to racial anxiety that the white nationalist subject articulates on new media: discovery, mapping, and mobilization . The essay concludes by outlining future directions for scholars of race and media who wish to study white nationalism on the internet.